PENERAPAN BERMAIN KATA BERBURU UNTUK MENINGKATKAN HASIL BELAJAR LOMPAT JAUH GAYA JONGKOK (Department of Physical Education, Sport, Health and Recreation, 2013)
The purpose of this research is to improve the learning outcomes of the long jump squat force in the Fourth grade students of Ngemplak Simongan 02 Elementary school Semarang with the application of frog hunting game. This study uses Classroom Action Research (CAR). The subjects in this study were fourth grade students of SDN 02 Ngemplak Simongan Semarang are 32 students to improve learning outcomes of the research object long jump squat style. Data collection techniques using documentation and observation through the assessment of learning outcomes of the cognitive, psychomotor and affective aspects of aspects in the long jump performance. The data analysis technique used in this study is quantitative data (values ​​student learning outcomes) that can be analyzed by descriptive and qualitative data. The results showed that through the application of game frog hunting learning model to improve learning outcomes basic motion long jump squat style from the first cycle to the second cycle. Learning outcomes long jump squat style in the first cycle in the complete category is 59.37% or 19 students and there are 13 unresolved child or 40.63%. In the second cycle there was an increase in the percentage of student learning outcomes in the category completed by 84.37% or 27 students and children who have not completed 5 or 15.63%. Conclusion of this research is the application of game hunting frogs can improve learning outcomes in the long jump squat force fourth grade students of SDN 02 Ngemplak Simongan Semarang.